Penyuluhan dan Sosialisasi Guna Meningkatkan Kesadaran Bahaya NAPZA bagi Remaja Desa Sumbersari - Muhammad Indra Setyaji; Eka Fhutri Kembari; Rosyfi Zakiyatul Af'idah; Firda Nuraisyah; Irawati Ainunita; M. Riyan Maulana; Ansia Aulia Dina; Defikha Dhya'ulhaq; Hamdan Husein Batubara (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Abuse of Narcotics, Psychotropics and Addictive Substances (Drugs) among the younger generation is a crucial issue that threatens the future of the nation. This abuse has a significant negative impact on the mental and physical development of the younger generation. Therefore, prevention efforts through education, routine counseling and positive activities in the community are very important. The socialization program on the dangers of drugs was carried out at the Sumbersari Village Hall, Ngampel District, Kendal Regency. The targets for this activity are teenagers from Sumbersari Village. This activity is carried out using the ABCD method which includes identifying community strengths, asset mapping, community economic analysis, creating relationships and activity priorities, as well as monitoring and evaluation. The results of counseling regarding the abuse of narcotics, psychotropic substances and other addictive substances in Sumbersari village show significant benefits for the younger generation. Participants' responses emphasized the importance of the understanding provided. The suitability of participants' expectations with the reality of the activity can be seen from the appreciation for the presence of food and similarities with socialization at school. Participants' understanding also increased thanks to the material presented in an interesting way. Comfort during activities is an important factor in maintaining participant concentration. However, participant satisfaction was affected by schedule discrepancies.